A new deep-bodied fossil fish (Actinopterygii) from the Rio do Rasto Formation, Paraná Basin, Brazil - Dias, Eliseu Vieira (Zootaxa, 2012)
Fossil fishes from the Paraná Basin are represented by actinopterygians, chondrichthyans, coelacanths and dipnoans. This diverseichthyofauna comprises mainly fragmentary material with few complete specimens. This paper presents a new Upper Permianray-finned fish from the Rio do Rasto Formation of the Paraná Basin, southern Brazil. The holotype and only known specimen ofParanaichthys longianalis gen. nov. et sp. nov. is an almost complete poorly preserved specimen of a deep-bodied fish that be-longs to the collection of the Museu de Ciências e Tecnologia-PUCRS, Porto Alegre, Brazil. The head is slightly deep posteriorlyand the oral cavity presents a crushing dentition. The anal fin is remarkably large and long. The heterocercal caudal fin presentsthe chordal and hypochordal lobe equally in size. Flank scales are deeper than long and covered with ganoine. The dermal bonesare also covered by ganoine and present elongated odontodes. The rostral region and the anterior portion of the mandible are cov-ered with conical odontodes. The elongated and long based anal fin is considered apomorphic for this new fish. A reconstructionattempting to correct taphonomic distortions is presented. The systematic relationships of the new taxon suggest that it is relatedto the platysomids. Its crushing dentition indicates a diet based on hardfood, such as conchostraceans and small mollusks, bothvery common in the Rio do Rasto Formation. The new genus and species inhabited rivers and lakes during the Wordian-Captanian (Guadalupian, Permian 268 to 260 M.y.).